2006
DOI: 10.1097/01.pec.0000202453.42108.f1
|View full text |Cite
|
Sign up to set email alerts
|

Psychosocial Needs of African American Youth Presenting to a Pediatric Emergency Department With Assault-related Injuries

Abstract: African American assault victims are experiencing a broad range of psychosocial needs. To bolster youth recovery and reduce the risk of future injury, researchers and practitioners need to identify effective methods of assessing these needs in the emergency department so that youth victims of interpersonal violence can be referred for appropriate follow-up services.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 24 publications
0
12
0
Order By: Relevance
“…The study also found that intervention may reduce aggression and problem behavior and increase self efficacy. Literature suggests that these youth are at high risk for repeated visits and injury,5 have significant psychosocial needs,36,37 and are less likely to have advised follow-up after ED treatment 38. The ED may be an important access point to these high risk youth and provides an opportunity to intervene.…”
Section: Commentmentioning
confidence: 99%
“…The study also found that intervention may reduce aggression and problem behavior and increase self efficacy. Literature suggests that these youth are at high risk for repeated visits and injury,5 have significant psychosocial needs,36,37 and are less likely to have advised follow-up after ED treatment 38. The ED may be an important access point to these high risk youth and provides an opportunity to intervene.…”
Section: Commentmentioning
confidence: 99%
“…618 The few ED-based studies of youth with acute assault-injuries have reported high levels of depressive symptoms, 1923 post-traumatic stress symptoms, 22,24 and alcohol/substance use. 19,22,25 Nonetheless, prior studies have been limited by: 1)the use of convenience samples; 2) the inclusion of only those with biological markers of substance use, alone; 3) interviewing patients long after the assault event took place; 4) the lack of use of diagnostic criteria for substance use/mental health disorders; 5) the lack of a non-injured comparison group of drug using youth.…”
Section: Introductionmentioning
confidence: 99%
“…(1)(2)(3)(4)(5)(6)(7)(8)(9) Beyond the physical trauma, violence carries significant lifelong implications for psychosocial development as evidenced by increased psychological and behavioral problems. (3,5,6,10) Obtaining adequate psychosocial, educational, and physical health resources for survivors of violent injury is difficult and many victims return to stressful home environments, making their recovery even more complex.…”
Section: Introductionmentioning
confidence: 99%